The Role of Mental Imagery in Depression: Negative Mental Imagery Induces Strong Implicit and Explicit Affect in Depression - Görgen, Stefanie Maria; Joormann, Jutta; Hiller, Wolfgang; Witthöft, Michael (Frontiers in Psychiatry, 2015)
Mental imagery, seeing with the mind’s eyes, can induce stronger positive as well as negative affect compared to verbal processing. Given this emotion-amplifying effect, it appears likely that mental images play an important role in affective disorders. According to the subcomponents model of depression, depressed mood is maintained by both negative imagery (which amplifies negative mood) and less efficient positive imagery processes. Empirical research on the link between mental imagery and affect in clinical depression, however, is still sparse. This study aimed at testing the role of mental imagery in depression, using a modified version of the Affect Misattribution Procedure (AMP) and the Self-Assessment Manikin (SAM) to assess implicit (AMP) and explicit (SAM) affect elicited by mental images, pictures, and verbal processing in clinically depressed participants (n = 32) compared to healthy controls (n = 32). In individuals with a depressive disorder, compared to healthy controls, negative mental images induced stronger negative affect in the explicit as well as implicit measure. Negative mental imagery did not, however, elicit greater increases in explicitly and implicitly assessed negative affect compared to other processing modalities (verbal processing, pictures) in the depressed group. Additionally, a positive imagery deficit in depression was observed in the explicit measure. Interestingly, the two groups did not differ in implicitly assessed affect after positive imagery, indicating that depressed individuals might benefit from positive imagery on an implicit or automatic level. Overall, our findings suggest that mental imagery also plays an important role in depression and confirm the potential of novel treatment approaches for depression such as the promotion of positive imagery.